THE USE OF AN OPEN SOURCE FEA SOLVER ON A STANDARD ENGINEERING PROBLEM (Perner's Contacts, 2022)
The article deals with a FEA results comparison of an open source FEM software CODE_ASTER with a commercial software SolidWorks Simulation and Abaqus. The problem of a statically loaded spherical cap is solved. Result evaluation is aimed at loss of stability, i.e. limit load (equilibrium curve) when loss of stability occurs and its corresponding shape of deformation. The response of the structure is described by a load-deflection curve of a top of a spherical cap in axial direction.